Pola Komunikasi Keluarga Terhadap Remaja Pecandu Game Online di Desa Tiram, Tukak Sadai, Bangalore Selatan - Kurdeniansyah Kurdeniansyah; Joko Mohamat Santoso; Pingky Romadhan (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
The phenomenon of online gaming addiction among adolescents in Tiram Village yields various psychosocial repercussions, including a decline in academic performance, diminished social interactions, and deteriorating family intimacy, notably in the intensity of communication. The dynamics of family communication patterns concerning adolescents addicted to online gaming constitute a critical issue that necessitates comprehensive investigation. This study analyzes the focal problem by employing McLeod and Chaffee’s Family Communication Patterns Theory, which encompasses four distinct communicative typologies: consensual, pluralistic, protective, and laissez-faire. This research adopts a descriptive qualitative approach, utilizing in-depth interviews with parents and adolescents exhibiting tendencies toward online gaming addiction. Furthermore, the researcher conducted casual observations, ensuring the trustworthiness and validity of the collected data through prolonged engagement in the research locale. The findings indicate that family communication patterns play a pivotal role in shaping online gaming addiction behaviors among adolescents in Tiram Village, Tukak Sadai Subdistrict, South Bangka Regency.